FUNCTIONAL FEATURES OF NEOLOGISMS AND ABBREVIATIONS IN SOCIAL MEDIA DISCOURSE (BASED ON UZBEK AND ENGLISH CORPORA) (International journal of artificial intelligence, 2026)
This study explores the functional characteristics of neologisms and abbreviations in social media discourse, drawing on corpora in both Uzbek and English. The research analyzes how new lexical units and shortened forms emerge, spread, and function in online communication, reflecting socio-cultural trends, digital communication strategies, and language innovation. Comparative analysis reveals similarities and differences in the usage patterns of neologisms and abbreviations across the two languages, highlighting the influence of context, audience, and platform-specific conventions. The findings contribute to a deeper understanding of contemporary language dynamics in digital spaces and offer insights for linguists, educators, and communication specialists.